The Effect of Metformin Use on Mortality of COVID-19 Patients with Diabetes Mellitus - Dini Hapsari; Dwi Trisnawati Zainal (Journal of Epidemiology and Public Health, 2022)
Background: COVID-19 is a disease caused by infection with the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). COVID-19 is still a worldwide threat because of its high morbidity and mortality. This is influenced by the occurrence of hypertension, obesity, age and diabetes mellitus. However, currently there is still controversy in the results of research regarding the use of metformin in COVID-19 with type 2 diabetes mellitus (type 2 DM). This study was aimed to analyze the effect of metformin in COVID-19 patients with diabetes mellitus on mortality rates.Subjects and Method: This study was a systematic review and meta-analysis with the following PICO. P: COVID-19 patient with type-2 diabetes mellitus. I: administration of metformin therapy. C: therapy other than metformin and O: mortality. The articles used in this study were obtained from several databases, namely PubMed, Science Direct, Proquest, SpringerLink, Google Scholar and Scopus. The article search keywords were: “COVID-19” OR “coronavirus” AND “diabetes” AND “metformin” AND “mortality.” Articles included are full-text English using a cohort study design from 2020 to 2021 and reporting the Odds Ratio in multivariate analysis. The selection of articles was carried out using the PRISMA flow chart. The articles were analyzed using the Review Manager 5.3 application.Results: A total of 7 cohort studies involving 136,321 COVID-19 patients from the Americas (USA and Alabama United States), Europe (France and Spain), and Asia (China and South Korea) were selected for systematic review and meta-analysis. The data collected showed that COVID-19 patients with diabetes mellitus who were given metformin reduced the risk of death by 0.90 times higher compared to COVID-19 patients with diabetes mellitus who were not given metformin therapy (aOR= 0.90; CI 95%= 0.68 to 1.19; p=0.450).Conclusion: Metformin can reduce the risk of death in COVID-19 patients with diabetes mellitus. Keywords: Diabetes, COVID-19, SARS-CoV-2, metformin, mortality Correspondence:Dwi Trisnawati Zainal. Masters Program of Public Health Science, Universitas Sebelas Maret. Jl. Ir. Sutami 36A Surakarta 57126, Central Java. Email: dwitrisnawatiz@gmail.com. Mobile: +62-8133-1282-009.